Analisis Keuntungan Tak Terduga Yang Didapat Perusahaan Ekspor Tambang Batubara Di Indonesia Pada Periode 2020-2022 - Vera Maytara; Juliana Nasution; Budi Dharma (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2023)
It will be a breath of fresh air for coal mining enterprises all around the world, including Indonesia, when global coal prices rise in 2021. This gain is referred to as a windfall profit since causes outside of the miner's control are what led to it. The COVID-19 epidemic, on the other hand, has led the Indonesian economy to contract, having an effect on output, exports, and the new wind in coal prices tied to the exchange rate. Due to this disparity, investigation was done to see if the unexpected earnings that Indonesian mining firms experienced were liable to reserve tax. The approach of literature study or literature review was employed in this study.Â  This study will demonstrate that the application of windfall tax to coal exports is effective by looking at the situation of coal mining companies in Indonesia, the application of windfall tax in other nations, and taking into account the coal company tax regulations that apply in Indonesia. It may be used to generate cash for the government and supply domestic coal as feedstock for automated stabilizers. Additionally, it will have an impact on coal export prices and output between 2020 and 2022. Based on this research, a temporary sasaraned supplementary income tax for short-term goals and a permanent tax for long-term goals can be imposed.